Vie d'Ernest Solvay 1838-1922 - Héger, Paul; Lefebure, Charles (Bruxelles : J.-E. Goosens, 1928)
Bibliotheek E. Anseele
Dedicator: Solvay, Ernest, dedicatee: Anseele, Edward (sr.)
Met bijlagen.
Nederlands
Monografie
Keywords: Solvay, Ernest